Pathogenicity and virulence of Yersinia - Jarett A. Seabaugh; Deborah M. Anderson (Virulence, 2024)
ABSTRACTThe genus Yersinia includes human, animal, insect, and plant pathogens as well as many symbionts and harmless bacteria. Within this genus are Yersinia enterocolitica and the Yersinia pseudotuberculosis complex, with four human pathogenic species that are highly related at the genomic level including the causative agent of plague, Yersinia pestis. Extensive laboratory, field work, and clinical research have been conducted to understand the underlying pathogenesis and zoonotic transmission of these pathogens. There are presently more than 500 whole genome sequences from which an evolutionary footprint can be developed that details shared and unique virulence properties. Whereas the virulence of Y. pestis now seems in apparent homoeostasis within its flea transmission cycle, substantial evolutionary changes that affect transmission and disease severity continue to ndergo apparent selective pressure within the other Yersiniae that cause intestinal diseases. In this review, we will summarize the present understanding of the virulence and pathogenesis of Yersinia, highlighting shared mechanisms of virulence and the differences that determine the infection niche and disease severity.